Estrategias pedagógicas para el Aprendizaje de la Automatización. (2011)
In order to obtain the right solution to automation problems, it is necessary to design a strategy that allows for selection of appropriate components and their integration to achieve the proposed objective. The knowledge taught to the automation engineering student at the La Salle University is given in a methodical, sequential and structured manner in such a way they can handle that knowledge and can solve problems of the productive sector. In this article, one of the strategies used in the program is described. With this strategy the students can learn about the different areas of knowledge involved in automation, in order to obtain automatic systems that are capable of providing adequate and efficient solutions to the demands of society.